A phase 2 study of dalantercept, an activin receptor‐like kinase‐1 ligand trap, in patients with recurrent or metastatic squamous cell carcinoma of the head and neck. Issue 23 (20th September 2016) - Jimeno, Antonio; Posner, Marshall R.; Wirth, Lori J.; Saba, Nabil F.; Cohen, Roger B.; Popa, Elizabeta C.; Argiris, Athanassios; Grossmann, Kenneth F.; Sukari, Ammar; Wilson, Dawn; Zhang, Xiaosha; Sun, Jade; et al.
Abstract : BACKGROUND: Patients with platinum‐refractory, recurrent or metastatic squamous cell carcinoma of the head and neck (RM‐SCCHN) have limited options. Activin receptor‐like kinase 1 (ALK1) is a type I receptor of the transforming growth factor β superfamily expressed on activated endothelial cells. Dalantercept is an ALK1 receptor fusion protein that acts as a ligand trap to block signaling through ALK1 and inhibits stages of angiogenesis involved in blood vessel maturation and stabilization. In a phase 1 study, dalantercept demonstrated clinical activity in patients with RM‐SCCHN. The objective of the current study was to evaluate the activity of dalantercept in RM‐SCCHN. METHODS: Forty‐six patients received dalantercept at doses of 80 mg (n = 2), 0.6 mg/kg (n = 13), or 1.2 mg/kg (n = 31) subcutaneously every 3 weeks. The primary endpoint was the overall response rate according to Response Evaluation Criteria in Solid Tumors (RECIST version 1.1). Secondary endpoints included progression‐free survival and overall survival, safety and tolerability, and pharmacokinetic and pharmacodynamic assessments. RESULTS: Forty patients were evaluable for response (13 who received dalantercept 0.6 mg/kg and 27 who received dalantercept 1.2 mg/kg). The overall response rate was 5% (n = 2), and 35% of patients had stable disease; 44% of patients who received 1.2 mg/kg and 30.8% of those who received 0.6 mg/kg achieved disease control (partial response or stable disease). The median progression‐fee survival was 1.4 months (95% confidence interval, 1.3‐2.2 months), and the median overall survival was 7.1 months (95% confidence interval, 5.5‐11.1 months). Drug‐related adverse events (>15%) were anemia, fatigue, peripheral edema, headache, and hyponatremia. CONCLUSIONS: In an unselected, heavily pretreated population of patients with RM‐SCCHN, dalantercept monotherapy resulted in a favorable safety profile but only modest dose‐dependent activity, and it did not meet the primary efficacy objective of the study. Cancer 2016;122:3641‐9. © 2016 American Cancer Society . Abstract : Activin receptor‐like kinase 1 (ALK1), a type I receptor of the TGF‐β superfamily, is expressed on activated endothelial cells in squamous cell carcinoma of the head and neck and is critical in several stages of angiogenesis, particularly those involved in blood vessel maturation and stabilization. The authors report a trial of dalantercept, a receptor fusion protein that acts as a ligand trap to block ALK1 signaling in patients with relapsed/metastatic squamous cell carcinoma of the head and neck. See also pages 3592‐5.